Role of life-skills and attitude toward alcohol abuse in predicting academic achievement of school students - Kishor Kumar Rai; Vandana (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Life skills are crucial for young adults to lead a successful, satisfying, and productive life. There is enough evidence suggesting a positive relationship between life skills and academic performance. Substance abuse among adolescents is a common problem that often leads to academic disorientation and delinquent behavior. This study aimed to determine whether life skills and attitudes toward alcohol abuse predicted school students' academic achievement. MATERIAL AND METHOD: The participants (N = 726) enrolled in senior secondary schools of Sikkim, a north-eastern state of India, constituted the population of the present study. Data were collected using the "Life Skills Assessment Scale" developed by Subashree and Nair (2014), and the "Attitude towards Alcohol Abuse Scale" developed by the investigators. RESULT: Life skills and attitude toward alcohol abuse significantly predict students' academic achievement. 15.3% variance in academic achievements of the students was explained by life skills and attitude toward alcohol abuse. Further, the t-test result reflects that both the variables had significant predictive power to predict students' academic achievement. CONCLUSION: The finding shows that there was a significant relationship between academic achievement and life skills and attitude toward alcohol abuse of school students. Life skills and attitude toward alcohol abuse predicted 15.3% of the variance in academic achievement.